Absorption, circular dichroism, and photoluminescence in perylene diimide bichromophores: polarization-dependent H- and J-aggregate behavior - Kistler, K A; Pochas, C M; Yamagata, H; Matsika, S; Spano, F C (The journal of physical chemistry. B, 2012)
Using a single-mode Holstein Hamiltonian with through-space excitonic couplings evaluated quantum mechanically, the absorption, circular dichroism, and photoluminescence spectral line shapes of a chiral perylene diimide dimer complex were accurately reproduced. In general, a dimer consisting of two chromophores related through a C(2) rotation is neither a J- nor an H-aggregate because oscillator strength is divided between the top and bottom of the exciton band. The division gives rise to the two Davydov components per vibronic band in the absorption spectrum. Nevertheless, it is shown that the vibronic structure of the absorption component polarized in the same direction as the lower (upper) Davydov component is identical to what one would obtain from an ideal J- (H-) aggregate. Emission generally contains both polarization components, but the component polarized in the same direction as the lower (upper) Davydov component behaves similarly to the emission from an ideal J- (H-) aggregate. The basic photophysical behavior also applies to molecular crystals containing two molecules per unit cell in which the interactions between inequivalent molecules dominate over interactions between equivalent molecules.